2022
DOI: 10.3390/ijerph19159641
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the COVID-19-Related Stigma Scale for Healthcare Workers (CSS-HCWs)

Abstract: Stigma among healthcare workers during the coronavirus disease 2019 (COVID-19) pandemic is an issue that requires immediate attention, as it may otherwise lead to the collapse of healthcare systems. In this study, we developed the COVID-19-related stigma scale for healthcare workers (CSS-HCWs) and assessed its reliability and validity. Data were collected online from 500 participants, including physicians and nurses involved in COVID-19 care. The first item of the draft scale was developed based on a literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A recent study from Japan developed and validated a new scale exploring the COVID-19-related stigma scale among HCWs. The new scale (18-items) showed high reliability for all factors (Cronbach α=0.970) and the coefficients for the sub-scales 'personal stigma', 'concerns of disclosure and attitude', and 'family stigma', were 0.940, 0.943, and 0.955, respectively 16 . Another group of researchers from the Middle East also developed and validated COVID-19 stigma scale to be used among HCWs working with COVID-19 patients.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study from Japan developed and validated a new scale exploring the COVID-19-related stigma scale among HCWs. The new scale (18-items) showed high reliability for all factors (Cronbach α=0.970) and the coefficients for the sub-scales 'personal stigma', 'concerns of disclosure and attitude', and 'family stigma', were 0.940, 0.943, and 0.955, respectively 16 . Another group of researchers from the Middle East also developed and validated COVID-19 stigma scale to be used among HCWs working with COVID-19 patients.…”
Section: Discussionmentioning
confidence: 88%
“…The positive coe cient of the two rounds of expert consultation was 100%, and the enthusiasm of experts to participate in this study was high. The authority coe cients of experts were 0.84, Cr ≥ 0.8, and the authority of the selected experts was high (Tsukuda et al, 2022). Kendall's harmony coe cient was 0.205 (p < 0.001), and the coe cient of variation was 0.125-0.248, all above 0.25, indicating that the experts' opinions were highly consistent, and the degree of coordination was good.…”
Section: Discussionmentioning
confidence: 97%
“…It should be mentioned that HCWs play a crucial role in putting awareness practices into place because they can predict the negative efects of stigmatization and lessen them through institutional and social media interventions [20]. In earlier research [27,28], it was also found that dental professionals and laboratory staf for infected persons during the pandemic experienced substantial COVID-19-related stigma [4,22].…”
Section: Discussionmentioning
confidence: 99%